Dimensions of biodiversity loss: Spatial mismatch in land‐use impacts on species, functional and phylogenetic diversity of European bees. Issue 12 (13th September 2017) - De Palma, Adriana; Kuhlmann, Michael; Bugter, Rob; Ferrier, Simon; Hoskins, Andrew J.; Potts, Simon G.; Roberts, Stuart P.M.; Schweiger, Oliver; Purvis, Andy
Abstract: Aim: Agricultural intensification and urbanization are important drivers of biodiversity change in Europe. Different aspects of bee community diversity vary in their sensitivity to these pressures, as well as independently influencing ecosystem service provision (pollination). To obtain a more comprehensive understanding of human impacts on bee diversity across Europe, we assess multiple, complementary indices of diversity. Location: One Thousand four hundred and forty six sites across Europe. Methods: We collated data on bee occurrence and abundance from the published literature and supplemented them with the PREDICTS database. Using Rao's Quadratic Entropy, we assessed how species, functional and phylogenetic diversity of 1, 446 bee communities respond to land‐use characteristics including land‐use class, cropland intensity, human population density and distance to roads. We combined these models with statistically downscaled estimates of land use in 2005 to estimate and map—at a scale of approximately 1 km 2 —the losses in diversity relative to semi‐natural/natural baseline (the predicted diversity of an uninhabited grid square, consisting only of semi‐natural/natural vegetation). Results: We show that—relative to the predicted local diversity in uninhabited semi‐natural/natural habitat—half of all EU27 countries have lost over 10% of their average local species diversity and two‐thirds of countries have lost over 5% of their average local functional and phylogenetic diversity. All diversity measures were generally lower in pasture and higher‐intensity cropland than in semi‐natural/natural vegetation, but facets of diversity showed less consistent responses to human population density. These differences have led to marked spatial mismatches in losses: losses in phylogenetic diversity were in some areas almost 20 percentage points (pp.) more severe than losses in species diversity, but in other areas losses were almost 40 pp. less severe. Main conclusions: These results highlight the importance of exploring multiple measures of diversity when prioritizing and evaluating conservation actions, as species‐diverse assemblages may be phylogenetically and functionally impoverished, potentially threatening pollination service provision.